2017
DOI: 10.1017/s0022215117001736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cardiovascular risks and recovery of idiopathic sudden sensorineural hearing loss in hospitalised patients: comparison between complete and partial sudden sensorineural hearing loss

Abstract: The lack of a clear relationship between idiopathic sudden sensorineural hearing loss and cardiovascular risk factors suggests that sudden sensorineural hearing loss has a predominantly multifactorial disease profile regardless of hearing impairment severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
(26 reference statements)
0
8
0
1
Order By: Relevance
“…Many researchers have tried to explain the relationship of SSNHL with diseases carrying CVR-factor such as HT, DM, and HL by vascular-inflammatory hypotheses. 5,[9][10][11][12] Haremza et al 5 suggested that SSNHL should be considered as an early vascular symptom that elicits CVR factors such as HL and HT, which are unknown before. Lin et al 10 reported that DM increased the risk of SSNHL and Ryu et al 11 suggested that hyperglycemia could be a potential negative prognostic factor Abbreviations: Difference, Tukey test; F, one-way variance analysis (ANOVA); G1, Group 1; G2, Group 2; G3, Group 3; G4, Group 4; L, lymphocyte; n, number of patients; N, neutrophil; NLR, neutrophil to lymphocyte ratio; P, significance level; Plt, platelet; PLR, platelet to lymphocyte ratio; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many researchers have tried to explain the relationship of SSNHL with diseases carrying CVR-factor such as HT, DM, and HL by vascular-inflammatory hypotheses. 5,[9][10][11][12] Haremza et al 5 suggested that SSNHL should be considered as an early vascular symptom that elicits CVR factors such as HL and HT, which are unknown before. Lin et al 10 reported that DM increased the risk of SSNHL and Ryu et al 11 suggested that hyperglycemia could be a potential negative prognostic factor Abbreviations: Difference, Tukey test; F, one-way variance analysis (ANOVA); G1, Group 1; G2, Group 2; G3, Group 3; G4, Group 4; L, lymphocyte; n, number of patients; N, neutrophil; NLR, neutrophil to lymphocyte ratio; P, significance level; Plt, platelet; PLR, platelet to lymphocyte ratio; SD, standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In SSNHL development, vascular, infectious, autoimmune, traumatic, metabolic, hematologic, and neurological mechanisms have been suggested and is still being discussed. [3][4][5][6] Advanced ages, vertigo at the onset, degree of hearing loss, audiometric configuration, duration between onset, and treatment are known to be important for the prognosis. [2][3][4] On the other hand, the prevalence of hearing loss is reported to be high in males, Caucasians, smokers, and patients with older age, low educational level, diabetes mellitus (DM), and hypertension (HT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of DM was reported higher among the patients with SSNHL [28]. Aimoni et al [6] found that the prevalence of DM was 15.6% among the patients with SSNHL, whereas it was 8.5% among the control group.…”
Section: Discussionmentioning
confidence: 95%
“…A hirtelen halláscsökkenéssel diagnosztizált betegeink 59,1%-a rendelkezett ismert szív-ér rendszeri betegséggel. Ez az irodalomban található értékeknél magasabb arányt mutat, Göde kutatásában a betegek 30,4%-ának, Haremza vizsgálatában a betegek 27,5%-ának volt ismert cardiovascularis társbetegsége [18,19]. A társuló szív-ér rendszeri betegség miatt kezelt betegeknél kisebb mértékű hallásjavulás várható [12,13].…”
Section: áBraunclassified